1998
DOI: 10.1001/archfami.7.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Use of Acetaminophen and Nonsteroidal Anti-inflammatory Drugs: A Prospective Study and the Risk of Symptomatic Diverticular Disease in Men

Abstract: These results suggest that regular and consistent use of NSAIDs in general and acetaminophen is associated with symptoms of severe diverticular disease, particularly bleeding. Further research is needed to investigate the potentially deleterious effect of NSAIDs and other medications on the lower gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 44 publications
2
53
1
9
Order By: Relevance
“…In a casecontrol study in Japan, risk factors for DH included the use of ATDs and NSAIDs, hypertension, diabetes, arteriosclerotic diseases such as ischemic disease mellitus and chronic kidney disease, age ≥ 70 years, obesity [13,15,17,18] . Our study also found higher rates of use for both ATDs and NSAIDs, higher age and male sex, obesity, smoking, alcohol drinking, and arteriosclerotic diseases in patients with colonic DH compared to those with bleeding from other causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a casecontrol study in Japan, risk factors for DH included the use of ATDs and NSAIDs, hypertension, diabetes, arteriosclerotic diseases such as ischemic disease mellitus and chronic kidney disease, age ≥ 70 years, obesity [13,15,17,18] . Our study also found higher rates of use for both ATDs and NSAIDs, higher age and male sex, obesity, smoking, alcohol drinking, and arteriosclerotic diseases in patients with colonic DH compared to those with bleeding from other causes.…”
Section: Discussionmentioning
confidence: 99%
“…Most NSAIDs inhibit prostaglandin synthesis, which disrupts the microcirculation and inhibits platelet aggregation. As a result, NSAIDs can lead to bleeding in patients with diverticulosis [17] . DH in Japan is more common in men, whereas in Western countries, DH occurs equally in men and women [21] .…”
Section: Peer-reviewmentioning
confidence: 99%
“…Although acetaminophen has been associated with dyspepsia (33)(34)(35)(36)(37), it is perceived by physicians as not GI toxic (5,38) and, therefore, GPAs are not coprescribed with acetaminophen for gastroprotection. In this study, coprescriptions of GPAs with acetaminophen were considered as baseline prescriptions not related to acetaminophen use.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data have also implicated these agents in diverticular bleeding (95,96). Whether patients with diverticulosis should be counseled to avoid NSAIDs, as is done for ulcer patients, is still conjecture, as is the potential role of selective COX-2 antagonist NSAIDs.…”
Section: Hemorrhagementioning
confidence: 99%